Informatics in control, automation and robotics : 13th International Conference, ICINCO 2016 Lisbon, Portugal, 29-31 July, 2016 /: 13th International Conference, ICINCO 2016 Lisbon, Portugal, 29-31 July, 2016. ([2018]) - Unknown
No abstract available